2017
DOI: 10.1038/s41598-017-02104-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligand chain length drives activation of lipid G protein-coupled receptors

Abstract: Sphingosine-1-phosphate (S1P) is a lipid mediator that can activate five cell membrane G protein-coupled receptors (GPCRs) which carry a variety of essential functions and are promising drug targets. S1P is composed of a polar zwitterionic head-group and a hydrophobic alkyl chain. This implies an activation mechanism of its cognate receptor that must be significantly different from what is known for prototypical GPCRs (ie receptor to small hydrophilic ligands). Here we aim to identify the structural features r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 51 publications
4
48
5
Order By: Relevance
“…However, these results are contradictive to a recent report that S1P d20:1 has a lower potency but higher efficacy at S1P 2 compared to S1P d18:1 . This discrepancy is to some degree explainable by different concentrations applied, that is, the higher efficacy of S1P d20:1 demonstrated by Troupiotis‐Tsaïlaki et al was shown only at concentrations above 1 µM.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…However, these results are contradictive to a recent report that S1P d20:1 has a lower potency but higher efficacy at S1P 2 compared to S1P d18:1 . This discrepancy is to some degree explainable by different concentrations applied, that is, the higher efficacy of S1P d20:1 demonstrated by Troupiotis‐Tsaïlaki et al was shown only at concentrations above 1 µM.…”
Section: Discussioncontrasting
confidence: 56%
“…We propose that some of these functions could be mediated by changes in S1P signaling, as C18‐LCBs will finally lead to S1P d18:1 and C20‐LCBs to S1P d20:1. In this context, one recent study showed that S1P with C16‐ to C20‐LCBs differ in their ability to activate the S1P receptors . However, to our knowledge, quantitative data on the concentrations of sphingolipids with C20‐LCBs in the organism are sparse and contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective binding of a substrate to S1P 1 requires polar interactions between a ligand's hydrophilic head group and the residues located in the receptor's active site, while occupation of the interhelical transmembrane domain of the receptor dictates agonism or antagonism (Davis et al, 2007;Troupiotis-Tsaïlaki et al, 2017). Determining trends and similarities between similarly acting substrates helps to understand what structural features synthetic sphingoid analogs need to possess to specifically and agonistically -or antagonistically -target S1P 1 (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…While the polar active site serves as the inducing binding event of a substrate to S1P1, the interaction of the lipid tail of the ligand with the hydrophobic transmembrane domain of the receptor determines agonism versus antagonism (Truc-Chi et al, 2008;Yuan et al, 2013;Troupiotis-Tsaïlaki et al, 2017). From the crystal structure of the S1P 1 in conformation with antagonist ML056 (W146) and from previous MD experiments with S1P, it is concluded that the hydrophobic tail of potential S1PR ligands inserts into a mostly aromatic binding pocket formed by residues from the transmembrane helices TM3, TM5, TM6, and TM7; in particular, residues F125 3.33 , F210 5.47 , and F273 6.52 form a cluster centered around TM5 that is highly responsive to the shape and length of a substrate's lipid tail (Hanson et al, 2012;Yuan et al, 2013;Troupiotis-Tsaïlaki et al, 2017). This observation was confirmed in our docking experiments; the C8 alkyl chains of all docked substrates, including unphosphorylated compounds, were consistently found embedded between phenylalanine residues F125 3.33 , F210 5.47 , and F273 6.52 .…”
Section: Lipophilic Tail Interactionsmentioning
confidence: 99%